Developing Supporting Groups: a manual for facilitators and participants. - Leo, Colin (Scientia Militaria - South African Journal of Military Studies, 2011)
Howard Kirschenbaum and Barbara Glaser are co-directors of the National Humanistic Educational Centre in Saratoga Springs, New York. These co-directors have gained extensive experience in leading seminars and conducting workshops on humanistic education and parent education amongst other things. The book is published by University Associates Publishers and Consultants, who engage in international publishing and consulting in the areas of human relations training, research and education.